HUBUNGAN KEBIASAAN MAKAN, PAPARAN MEDIA SOSIAL, DAN TEMAN SEBAYA DENGAN STATUS GIZI MAHASISWA PROGRAM STUDI GIZI UPN VETERAN JAKARTA - Gagar Milenianti Artadini, (2022)
Nutritional status is a condition in the human body that can be seen from food and the use of nutrients consumed in the body. Adolescent nutritional status can be influenced by various factors such as eating habits, exposure to social media, and also peers. Poor eating habits as well as social media exposure and peers influence play a role in unhealthy food choices and can increase the risk of overnutrition in adolescents. The purpose of this study was to determine the relationship between eating habits, social media exposure, and peers with the nutritional status of nutrition students UPN Veteran Jakarta. This study used a cross-sectional design which was taken with a stratified random sampling technique and sample with 117 respondents. Data was collected by filling out questionnaires and anthropometric measurements. Data processing using chi-square test. Based on the results of statistical tests, there is no relationship between eating habits and nutritional status (p-value = 0.148). There is a relationship between exposure to social media (p-value=0.037), peers (p-value=0.000) and nutritional status. Adolescents need to have a good friendship environment so that they can influence their behavior to be good, and can control time and be wisely in using social media.